2015
DOI: 10.1111/mpp.12248
|View full text |Cite
|
Sign up to set email alerts
|

Two thiadiazole compounds promote rice defence against Xanthomonas oryzae pv. oryzae by suppressing the bacterium's production of extracellular polysaccharides

Abstract: Thiazole, isothiazole, thiadiazole, and their derivatives are used to control various human, animal and plant diseases. In addition to having direct anti-microbial and anti-fungal properties, these compounds are thought to induce host defences, but the mechanism of defence induction remains poorly understood. This article reports that the thiadiazoles of zinc thiazole and bismerthiazol induce H2 O2 accumulation, up-regulation of defence-related genes, callose deposition and hypersensitive response-like cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Interestingly, the expression of all 13 genes was inhibited by bismerthiazol. A previous study has reported that bismerthiazol promotes rice defence by suppressing the bacterium's production of EPS (Liang et al ., ). In the current study, we found that the hut operons did not affect the production of EPS in Xoo (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, the expression of all 13 genes was inhibited by bismerthiazol. A previous study has reported that bismerthiazol promotes rice defence by suppressing the bacterium's production of EPS (Liang et al ., ). In the current study, we found that the hut operons did not affect the production of EPS in Xoo (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…D). A previous study has reported that bismerthiazol does not reduce the EPS production of 2‐1‐1 (Liang et al ., ). We therefore infer that bismerthiazol does not inhibit the QS of 2‐1‐1.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations